2019
DOI: 10.1016/j.jcis.2019.08.070
|View full text |Cite
|
Sign up to set email alerts
|

Fatty acid ester surfactants derived from raffinose: Synthesis, characterization and structure-property profiles

Abstract: Hypothesis: The development of functional and nutritional surfactants for the food industry remains a subject of great interest. Herein, therefore, we report on the design and synthesis of novel trisaccharide (raffinose) monoester-based surfactants in the expectation that they would display functional properties superior to certain disaccharide-based, commercially-deployed emulsifiers and thus have potential for industrial applications. Experiments: The title esters were prepared by enzymatic methods and their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 41 publications
0
10
0
Order By: Relevance
“…Specifically, after treating the cells with 150 μM ester 6 , the level of cyclin D1 decreased by 80%, while that of cyclin E fell by 40%. It is known that cyclin-dependent kinase 2 (CDK 2) combines with cyclin E, while CDK4 combines with cyclin D1 to form complexes that accompany the G1-S phase progression of cells. As such, ester 6 must decrease the level of CDK4 preferentially over that of CDK2. Overall, then, the observed G1 phase arrest in MCF-7 breast cancer cells by compound 6 occurs via simultaneous downregulation of cyclin E, cyclin D1, and CDK4.…”
Section: Resultsmentioning
confidence: 99%
“…Specifically, after treating the cells with 150 μM ester 6 , the level of cyclin D1 decreased by 80%, while that of cyclin E fell by 40%. It is known that cyclin-dependent kinase 2 (CDK 2) combines with cyclin E, while CDK4 combines with cyclin D1 to form complexes that accompany the G1-S phase progression of cells. As such, ester 6 must decrease the level of CDK4 preferentially over that of CDK2. Overall, then, the observed G1 phase arrest in MCF-7 breast cancer cells by compound 6 occurs via simultaneous downregulation of cyclin E, cyclin D1, and CDK4.…”
Section: Resultsmentioning
confidence: 99%
“…As shown by thin layer chromatography–mass spectrometry (TLC-MS), wild-type EstCE1 could also catalyze the monoacetylation of maltose and maltotriose (Figure S8). Esters of oligosaccharides have significant potential for applications as, for example, emulsifiers . By comparing wild-type EstCE1 and EstCE1-MAA in reactions of ethyl acetate with glucose/maltose/maltotriose, we observed that EstCE1-MAA outperformed the wild type for all three sugars (Figure ).…”
mentioning
confidence: 89%
“…The use of soapstock as a source of FFAs for the synthesis of fine chemicals is to be further investigated to expand the variety of products that can be obtained. The possibility to prepare other biodegradable surfactants [83], monomers for bio-based biodegradable new-generation polymers [84,85], and additives for the cosmetic industry [86][87][88] has to be carefully investigated.…”
Section: Conclusion and Future Prospectsmentioning
confidence: 99%